Effects of bio-organics and micronutrients on yield and nutrient uptake by mustard on loamy-sand soil of Rajasthan - Surendra Kumar Kumawat; S.R. Naga (Annals of Agricultural Research, 2023)
A field experiment was conducted under loamy sand soil during two consecutive rabi seasons at Agronomy Farm, S.K.N. of College of Agriculture, Jobner, India. The experiment comprising 20 treatments combination replicated three times, was laid out in the split-plot design with five treatments of bio-organic (control, FYM @ 10 t/ha, vermicompost @ 5 t/ha, FYM @ 10 t/ha + Azotobacter + VAM and vermicompost @ 5 t/ha + Azotobacter + VAM) and four treatments of micronutrients (Control, ZnSO4 @ 25 kg/ha, FeSO4 @ 50 kg/ha and ZnSO4 @ 25 kg/ha + FeSO4 @ 50 kg/ha). The significantly highest seed and stover yields, nutrients (N, P, K, S, Zn & Fe) content as well as uptake by mustard over control were recorded with the application of vermicompost @ 5 t/ha + Azotobacter + VAM. The application of ZnSO4 @ 25 kg/ha + FeSO4 @ 50 kg/ha registered significantly highest seed and stover yields, nutrients (N, K, S, Zn & Fe) content and Nutrient (N, P, K, S, Zn & Fe) uptake in seed & stover over rest of the treatments. Whereas, phosphorus concentration in both seed and stover decreased significantly with application of M3 (ZuSO4 @ 25 kg/ha + FeSO4 @ 50 kg/ha). Based on the experimental results, it is concluded that for substantial improvement in yields and nutrients (N, P, K, S, Zn & Fe) content as well as uptake by mustard individual and conjoint application of the treatment vermicompost @ 5 t/ha + Azotobactor + VAM (B4 ) and ZnSO4 @ 25 kg/ha + FeSO4 @ 50 kg/ha(M3 ) is required.